EFFECT OF USING GAMMA-IRRADIATED MIXTURE EXTRACT OF CAROB AND ROSELLE IN DIABETIC RATS - R.G.HAMZA; M.N. AL-SEENI (International Journal of Pharma and Bio Sciences, 2015)
This study aimed to investigate the antidiabetic and antioxidant effects of gamma irradiated mixture of carob and roselle (10 kGy) in diabetic male rats. The results with test rats indicated that alloxan administration induced the elevation of glucose level, activity of some liver enzymes and malondialdehyde concentration, while the level of insulin, testosterone and glutathione content (GSH) and the activity of superoxide dismutase (SOD) and catalase (CAT) were decreased under the effect of alloxan. As a result of treatment of diabetic rats with either raw or γ-irradiated mixture extract of carob and roselle (10 ml/Kg b.wt., for 6 weeks), hyperglycemia, hepatic and endocrine abnormalities induced by alloxan were improved. The results support the conclusion that raw and γ-irradiated mixture extract of carob and roselle can effect a partial normalization of the biochemical changes associated with alloxan-induced diabetes mellitus in rats. Furthermore, gamma-irradiation (10 kGy) increases the total phenolic content of dried carob and roselle.